The Relationship Between Staff Skills and Patient Satisfaction in Venous Blood Collection Procedures - Ketut Indrawati; Diah Prihatiningsih; I Gst Pt Agus Ferry Sutrisna Putra (Jurnal Kesehatan Cendikia Jenius, 2026)
Introduction: Venous blood sampling services are an important procedure in laboratory services because staff skills influence patient comfort and the quality of examination results. This study is necessary to determine the relationship between staff skills and patient satisfaction in primary healthcare settings.Objective: This study aims to analyze the relationship between staff skills and patient satisfaction levels in venous blood sampling procedures. Methods: This study used a descriptive correlational design with a cross-sectional approach. The sample consisted of 52 respondents selected using purposive sampling. Data were collected through staff skills and patient satisfaction questionnaires during the 2025–2026 research period and were analyzed using the Spearman Rank test. Results: The results showed that staff skills were mostly categorized as very good (51.9%) and good (40.4%), while patient satisfaction was dominated by satisfied (50.0%) and very satisfied (46.2%) categories. The Spearman Rank test showed p=0.000 with a correlation coefficient of 0.956, indicating a very strong and positive relationship. Conclusion: It can be concluded that improving staff skills impacts patient satisfaction; therefore, continuous training and routine evaluation are recommended to maintain service quality.